(untitled) (Nexo Revista Científica, 2022)
In the era of digitalization of the global economy, companies are beginning to create their digital platforms and digital ecosystems, transferring the main activities of the company to the digital environment to maintain global competitiveness. The study of the patterns and principles of the development of digital ecosystems is relevant for business from the point of view of creating its peculiar sustainable competitive advantage. The object of the study is digital ecosystems. The subject of the study is the features and trends of the development of digital ecosystems in the modern economy. The purpose of this work is to identify patterns of development of digital ecosystems and make recommendations for companies that want to create their digital ecosystems. The study of annual reports, conducting in-depth interviews and statistical analysis of the stock price allowed us to achieve the set purpose. The results of the study will be useful for representatives of traditional companies to implement projects to create their digital ecosystems, representatives of government agencies to regulate the activities of digital ecosystems, and for startups that are building new business models in the digital economy.